Beyond methods : macrostrategies for language teaching - Kumaravadivelu, B., 1948- (New Haven : Yale University Press, 2003)
Publisher's description: In this original book, B. Kumaravadivelu presents a macrostrategic framework designed to help both beginning and experienced teachers develop a systematic, coherent, and personal theory of practice. His book provides the tools a teacher needs in order to self-observe, self-analyze, and self-evaluate his or her own teaching acts. The framework consists of ten macrostrategies based on current theoretical, empirical, and experiential knowledge of second language and foreign language teaching. These strategies enable teachers to evaluate classroom practices and to generate techniques and activities for realizing teaching goals. With checklists, surveys, projects, and reflective tasks to encourage critical thinking, the book is both practical and accessible. Teachers and future teachers, researchers, and teacher educators will find the volume indispensable.
Conceptualizing teaching acts -- Understanding postmethod pedagogy -- Maximizing learning opportunities -- Minimizing perceptual mismatches -- Facilitating negotiated interaction -- Promoting learner autonomy -- Fostering language awareness -- Activating intuitive heuristics -- Contextualizing linguistic input -- Integrating language skills -- Ensuring social relevance -- Raising cultural consciousness -- Monitoring teaching acts.
Includes bibliographical references (pages [319]-330) and index.
Keywords: Language and languages -- Study and teaching